Schistosoma mansoni Infection Can Jeopardize the Duration of Protective Levels of Antibody Responses to Immunizations against Hepatitis B and Tetanus Toxoid. - Diana K Riner; Eric M Ndombi; Jennifer M Carter; Amos Omondi; Nupur Kittur; Emmy Kavere; Harrison K Korir; Briana Flaherty; Diana Karanja; Daniel G Colley (Public Library of Science (PLoS), 2016)
Schistosomiasis is a disease of major public health importance in sub-Saharan Africa. Immunoregulation begins early in schistosome infection and is characterized by hyporesponsiveness to parasite and bystander antigens, suggesting that a schistosome infection at the time of immunization could negatively impact the induction of protective vaccine responses. This study examined whether having a Schistosoma mansoni infection at the time of immunization with hepatitis B and tetanus toxoid (TT) vaccines impacts an individual's ability to achieve and maintain protective antibody levels against hepatitis B surface antigen or TT.Adults were recruited from Kisumu Polytechnic College in Western Kenya. At enrollment, participants were screened for schistosomiasis and soil transmitted helminths (STHs) and assigned to groups based on helminth status. The vaccines were then administered and helminth infections treated a week after the first hepatitis B boost. Over an 8 month period, 3 blood specimens were obtained for the evaluation of humoral and cytokine responses to the vaccine antigens and for immunophenotyping.146 individuals were available for final analysis and 26% were S. mansoni positive (Sm+). Schistosomiasis did not impede the generation of initial minimum protective antibody levels to either hepatitis B or TT vaccines. However, median hepatitis B surface antibody levels were significantly lower in the Sm+ group after the first boost and remained lower, but not significantly lower, following praziquantel (PZQ) treatment and final boost. In addition, 8 months following TT boost and 7 months following PZQ treatment, Sm+ individuals were more likely to have anti-TT antibody levels fall below levels considered optimal for long term protection. IL-5 levels in response to in vitro TT stimulation of whole blood were significantly higher in the Sm+ group at the 8 month time period as well.Individuals with schistosomiasis at the start the immunizations were capable of responding appropriately to the vaccines as measured by antibody responses. However, they may be at risk of a more rapid decline in antibody levels over time, suggesting that treating schistosome infections with praziquantel before immunizations could be beneficial. The timing of the treatment as well as its full impact on the maintenance of antibodies against vaccine antigens remains to be elucidated.